Characterization of cumulus cloud fields using trajectories in the center of gravity versus water mass phase space: 2. Aerosol effects on warm convective clouds. Issue 11 (7th June 2016) - Heiblum, Reuven H.; Altaratz, Orit; Koren, Ilan; Feingold, Graham; Kostinski, Alexander B.; Khain, Alexander P.; Ovchinnikov, Mikhail; Fredj, Erick; Dagan, Guy; Pinto, Lital; Yaish, Ricki; Chen, Qian
Abstract: In Part I of this work a 3‐D cloud tracking algorithm and phase space of center of gravity altitude versus cloud liquid water mass (CvM space) were introduced and described in detail. We showed how new physical insight can be gained by following cloud trajectories in the CvM space. Here this approach is used to investigate aerosol effects on cloud fields of warm cumuli. We show a clear effect of the aerosol loading on the shape and size of CvM clusters. We also find fundamental differences in the CvM space between simulations using bin versus bulk microphysical schemes, with the bin scheme precipitation expressing much higher sensitivity to changes in aerosol concentrations. Using the bin microphysical scheme, we find that the increase in cloud center of gravity altitude with increase in aerosol concentrations occurs for a wide range of cloud sizes. This is attributed to reduced sedimentation, increased buoyancy and vertical velocities, and increased environmental instability, all of which are tightly coupled to inhibition of precipitation processes and subsequent feedbacks of clouds on their environment. Many of the physical processes shown here are consistent with processes typically associated with cloud invigoration. Key Points: Aerosol effects on clouds as reflected in the cloud center of gravity versus mass phase space Aerosol concentration correlates with cloud center of gravity during cloud growing stage Indications of aerosol induced warm cloud invigoration